2016
DOI: 10.3109/02813432.2015.1132891
|View full text |Cite
|
Sign up to set email alerts
|

Nurses in municipal care of the elderly act as pharmacovigilant intermediaries: a qualitative study of medication management

Abstract: ObjectiveTo explore registered nurses’ experience of medication management in municipal care of the elderly in Sweden, with a focus on their pharmacovigilant activities.DesignA qualitative approach using focus-group discussions was chosen in order to provide in-depth information. Data were analysed by qualitative content analysis.SettingFive focus groups in five different long-term care settings in two regions in Sweden.SubjectA total of 21 registered nurses (RNs), four men and 17 women, aged 27–65 years, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 24 publications
1
16
0
3
Order By: Relevance
“…), and that new strategies have been requested to facilitate their possibilities to do that (Johansson‐Pajala et al . ), the present study shows that a CDSS can be a useful tool in this endeavour. The results may be perceived as giving an overly positive picture of the RNs’ comprehension; however, this corresponds to previous findings, showing that RNs have a positive attitude towards informatics (Huryk ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…), and that new strategies have been requested to facilitate their possibilities to do that (Johansson‐Pajala et al . ), the present study shows that a CDSS can be a useful tool in this endeavour. The results may be perceived as giving an overly positive picture of the RNs’ comprehension; however, this corresponds to previous findings, showing that RNs have a positive attitude towards informatics (Huryk ).…”
Section: Discussionsupporting
confidence: 61%
“…, Johansson‐Pajala et al . ). In the present study, the CDSS was handled by the RNs, who additionally took on a great responsibility to view the reports and assess whether drug adjustments were required.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[26,27] Patients are often treated in silos by specialty, while no-one takes coordinated responsibility for their care. Similarly, problem solving is often restricted to the same silos.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the occupational therapists indicated that they took a supportive role in medication management by assisting the nurses. Johansson-Pajala, Blomgren, Bastholm-Rahmner, Fastbom, and Martin (2016) found that nurses believed they were more competent and more responsible than other members of the HHC team for medication management, making it difficult to trust members of the team who had insufficient understanding of the effects of medication on patient illnesses. Therefore, they often had to compensate for team members who lacked medication management knowledge and experience, further increasing their involvement in their patients' medication management.…”
Section: Cognitive Processmentioning
confidence: 99%